2003
DOI: 10.1139/z02-232
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of current and historical kit fox (Vulpes macrotis) dens in the Great Basin Desert

Abstract: Abstract:We examined the ecological and physical characteristics of den sites for 13 adult kit fox (Vulpes macmtis) in westem Utah from December 1998 to February 2001. We also compared current and historical den distribution among habitat types. The number of den sites used was not influenced by home-range size (P = 0.11) or season (P = 0.40), but was influenced by geographical area. Home-range size was smallest (P = 0.007) and the number of dens used was greatest (P = 0.009) in mountainous areas. Ecological a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
42
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(46 citation statements)
references
References 15 publications
3
42
0
1
Order By: Relevance
“…Predator-caused mortality was the highest cause of death for kit foxes during this study and coyotes have been shown to limit kit fox density [20], [22], [41], [45]. Mean home range size for kit foxes on the DPG was large (20.1 km 2 ); similar to earlier study [22] with a mean home range size of 22.6 km 2 for kit foxes on the DPG. Studies of kit foxes in other regions have reported much smaller home ranges between 4.6 km 2 [46] and 13.7 km 2 [47] with an average of 11.4 km 2 [22], [43], [44], [46]–[50].…”
Section: Discussionsupporting
confidence: 81%
“…Predator-caused mortality was the highest cause of death for kit foxes during this study and coyotes have been shown to limit kit fox density [20], [22], [41], [45]. Mean home range size for kit foxes on the DPG was large (20.1 km 2 ); similar to earlier study [22] with a mean home range size of 22.6 km 2 for kit foxes on the DPG. Studies of kit foxes in other regions have reported much smaller home ranges between 4.6 km 2 [46] and 13.7 km 2 [47] with an average of 11.4 km 2 [22], [43], [44], [46]–[50].…”
Section: Discussionsupporting
confidence: 81%
“…Despite considerable effort to understand the ecology of kit foxes in the Great Basin Desert (e.g., Arjo, Bennett, & Kozlowski, 2003;Egoscue, 1956Egoscue, , 1962Egoscue, , 1975 and the impacts of changing landscape and community dynamics (e.g., Arjo et al, 2007;Byerly et al, 2018;Kozlowski, Gese, & Arjo, 2012;Lonsinger et al, 2017), there has been a paucity of research into the genetic health of the kit fox population. Understanding the population genetic health of kit foxes is essential for developing effective conservation strategies.…”
Section: Introductionmentioning
confidence: 99%
“…Dissimilar to the species above, kit foxes utilize dens scattered throughout the landscape rather than single den complexes that comprise small spatial extents (Arjo et al. ). Our investigation corroborates previous findings that the adoption of a semi‐fossorial lifestyle can be subject to indirect effects, in that spending more time in burrows increases ectoparasite burden, and this burden in turn elicits a behavioral response of modifying den use behavior.…”
Section: Discussionmentioning
confidence: 99%
“…, Rodrick and Mathews , Arjo et al. ), the role of fleas in den use behavior, and consequently the hypothesis put forth by Egoscue () over fifty years ago, remains untested for this native mesocarnivore.…”
Section: Introductionmentioning
confidence: 99%